1990
DOI: 10.1068/a220829
|View full text |Cite
|
Sign up to set email alerts
|

Residential Property Values, the CBD, and Multiple Nodes: Further Analysis

Abstract: In this paper, a hedonic regression model of house prices in Los Angeles County is tested with use of 1970 and 1980 data on dwelling characteristics, neighborhood variables, and measures of accessibility to the central business district and subcenter nodes. Many of the coefficient estimates on the dwelling traits and neighborhood variables are robust, and where coefficients change there are obvious explanations. The most dramatic finding is that the distance to the CBD, with a weak but statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 3 publications
1
43
0
5
Order By: Relevance
“…Based on such results Heikkila et al (1989) claimed that the impact of workplace accessibility has been overemphasized. Richardson et al (1990) found a significantly negative value of the coefficient related to distance from the LA cbd in 1970, while this variable were not found to influence house prices in 1980. Waddell et al (1993) emphasized the importance of including the distance to secondary employment centers, and they found both a strong and significant asymmetric cbd-gradient, and strong effects from the non-cbd employment centers.…”
Section: Relevant Contributions In the Literaturementioning
confidence: 93%
“…Based on such results Heikkila et al (1989) claimed that the impact of workplace accessibility has been overemphasized. Richardson et al (1990) found a significantly negative value of the coefficient related to distance from the LA cbd in 1970, while this variable were not found to influence house prices in 1980. Waddell et al (1993) emphasized the importance of including the distance to secondary employment centers, and they found both a strong and significant asymmetric cbd-gradient, and strong effects from the non-cbd employment centers.…”
Section: Relevant Contributions In the Literaturementioning
confidence: 93%
“…Previous papers that to some extent are parallel to this approach are Dubin and Sung (1987), Heikkila et al (1989), Richardson et al (1990), Yinger (1992), Waddell et al (1993), and Krybokov (2010). Those contributions emphasize the importance of including distance to secondary employment centres in addition to the globally defined CBD gradient.…”
Section: Theoretical Foundations In the Literaturementioning
confidence: 99%
“…or/~n This is especmlly true for the Los Angeles Airport center show the airport center to have a larger impact than downtown, due to ~ts very small estimated gradients (about two percent per mile) lo Furthermore, accordmg to those estimates the influence of downtown Los Angeles declined over the decade, although ~ts impact remains maportant (second or third rank), n while that of the airport center increased over the decade However, the L A Aarport center seems to lose all its explanatory power t°We thought the importance of L A Airport might be due to its locatmn on the ocean shore, but its large impact remains even when we add a variable to the population density equation measuring distance to the ocean Furthermore, the Long Beach center, also located at the shore, does not have an especially large influence llHetld~la et at [18] and Richardson et al [32] examine housing prices, finding a similar decline m the influence of downtown L A from one of statistical sagmficance In 1970 to one of mslgnhficance in 1980 However, we interpret our results as indicating that downtown L A is still important m explaining population densities m 1980 its coetticlents are both statistically significant, and the estimated t statistic on IMPACT Is borderline, given the approximation revolved and the appropriateness of a one-sided test Hence downtown Los Angeles remained a potent If somewhat diminished influence on populatlon in 1980, and we must look to counteracting influences, such as amenmes, to expIam its weak effects on housing prices on employment when the heterscedastlcity correction is apphed Therefore, we remain dubious about suggestmns that downtown has been eclipsed by the airport m ~ts influence…”
Section: "~Ine-b"(r+l) = E -2 45 = 0 086mentioning
confidence: 99%